The Stylistic and Generic Iconography in Selected Religious Epics with an Emphasis on Allusion - Zahra Faraj Nezhad Farhang (مطالعات زبانی و بلاغی)
The unity manifested in the thought, the poetic vision, the expression of feelings, and the poetic perception of a poet determines his or her poetic style.  Style does not include the lexical items only; but is the product of various factors which wield an important influence on the audience. One such case is the relation between a word and its meaning. The type of words and literary terms used in a poem must correspond with its subject matter and form.   In this article, supposing that the lexicons used in the rhetorical pictures of epic poetry have been chosen in accordance with the condition, position, and decorum pertaining to them, after discussing a case of generic and stylistic icon, i. e. the relationship between a word and its meaning, the allusions in the religious epics: Tazian-nameh (a shortened version of Ibn Hassan Khossfi’s Khavaran-nameh), Raji Kermani’s Hamleh-ye Heydari, Mohammad Rafi Mashhadi’s complete edition of Hamleh-ye Heydari, and Khaje Rabi’s Ali-nameh have been researched and analyzed. A majority of the allusions has been mentioned alongside a consideration of the element of hyperbolic imagination and the concept of the rupture of habits-which is the soul and essential ingredient of an epic-and has been given expression to in epic terms.  Some of these allusions which contain themes dealing with military tools and equipments and adverbs of manner and also paradox, have gained an epic format.  Yet, some others, for instance the pictures related to the sunrise and sunshine, because of their very epic nature, have augmented the epicality of the allusions; these allusions, in addition to reflecting the mind of the poet and the customs and manners permeating the society, are in tune with the atmosphere of the epic poems.